Perbuatan Melawan Hukum sebagai Upaya Perlindungan terhadap Hak Subjektif - Kennedy, Alexander (CV. Lenggogeni Data Publishing, 2025)
The concept of Perbuatan Melawan Hukum (PMH) or tort in Indonesian civil law functions not only as a legal basis for claims of compensation but also as a mechanism to protect individuals’ subjective rights. Initially, “unlawful act” was narrowly interpreted as a violation of written laws; however, jurisprudential development, particularly since the landmark Lindenbaum vs Cohen (1919) case, has broadened its scope to include violations of propriety, morality, and rights recognized by society. This study examines the regulation of PMH under the Indonesian Civil Code (KUHPerdata) and its jurisprudential development, as well as its role in protecting subjective rights. Using a normative juridical method with statute and case approaches, the research draws on primary, secondary, and tertiary legal materials. The findings indicate that PMH serves a dual function, remedial (restoring losses) and preventive (deterring violations) and can protect subjective rights even when no specific legislation exists. However, challenges remain in proving fault, causation, and avoiding inconsistency in judicial decisions. The study recommends clear judicial guidelines, adaptive civil law reform, and enhanced judicial capacity to ensure consistent application of PMH as an instrument of rights protection within the framework of the rule of law. Keywords: Unlawful Act; Subjective Rights; Civil Law; Jurisprudence; Legal Protection. Abstrak Perbuatan Melawan Hukum (PMH) merupakan instrumen penting dalam hukum perdata Indonesia yang berfungsi tidak hanya sebagai dasar tuntutan ganti rugi, tetapi juga sebagai mekanisme perlindungan hak subjektif individu. Awalnya, konsep “melawan hukum” diartikan secara sempit sebagai pelanggaran terhadap peraturan tertulis, namun perkembangan yurisprudensi, khususnya sejak perkara Lindenbaum vs Cohen (1919), memperluas cakupannya hingga mencakup pelanggaran norma kepatutan, kesusilaan, dan hak yang diakui masyarakat. Permasalahan yang dikaji meliputi pengaturan PMH dalam KUHPerdata dan perkembangan penerapannya melalui yurisprudensi, serta perannya dalam melindungi hak subjektif. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan peraturan dan kasus, didukung analisis bahan hukum primer, sekunder, dan tersier. Hasil pembahasan menunjukkan bahwa PMH memiliki fungsi ganda, yaitu remedial (pemulihan kerugian) dan preventif (pencegahan pelanggaran), serta mampu melindungi hak subjektif meski belum diatur khusus dalam undang-undang. Namun, tantangan muncul pada pembuktian unsur kesalahan, hubungan kausal, dan potensi inkonsistensi putusan hakim. Disarankan adanya pedoman yudisial yang jelas, pembaruan hukum perdata yang adaptif, dan peningkatan kapasitas hakim untuk memastikan konsistensi penerapan PMH sebagai instrumen perlindungan hak dalam kerangka negara hukum.